SUB SISTEM INFORMASI PENGOLAHAN DATAPENJAJAGAN KENAIKAN GAJI BERKALA(KGB)PADA BAGIAN KEPEGAWAIAN SETDA KOTA TASIKMALAYA - Yusuf Sumaryana (JUTEKIN (Jurnal Teknik Informatika), 2014)
In an agency or a company, Human Resources also was instrumental agency or company for the purpose may be achieved. Human resources include employee. Employees in an gency or company is also very influential for life kelangsunagn agency or company. It required a Human Resources Information System.Implementation of Human Resources Information System is a system that helps an agency or company to produce information relating to employees, so that all users get the ease and get the desired information in the shortest possible time. In the preparation of the scientific paper entitled " Data Processing Information.Systems Sub Assessment Periodic Salary Increase in the Division of Human Resources Tasikmalaya Regional Secretariat " will be made an application in a simple program using Borland Delphi program that is expected to change the working system into computerized conventional and expected can also improve the working of the system has been running.Keyword : Human Resources Information System, Assessment Periodic Salary Increase. SUB SISTEM INFORMASI PENGOLAHAN DATAPENJAJAGAN KENAIKAN GAJI BERKALA(KGB)PADA BAGIAN KEPEGAWAIAN SETDA KOTA TASIKMALAYA